Drama Performance: Its Impacts on StudentsProficiency in the EFL Outside the Classroom Setting - I Ketut Warta (TEFLIN, 2002)
Abstract: Disability to function in oral and written English has been serious problems among students in higher education learning. This study is an attempt made to find out possible solutions to such problems through drama performance. The study is experimental in which subjects of different groups in the study were provided with different treatments. Data analysis show that students performance level developed from basic to intermediate, from being marginal user to modest.